WOMEN ENTREPRENEURSHIP FROM A GLOBAL PERSPECTIVE - ANU PANDEY, A. VENKAT RAMAN & VIJAY KUMAR KAUL (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, ECONOMICS & MANAGEMENT, 2013)
The number of women entrepreneurs is increasing all over the world but the rate of increase is not the same for all the countries. In some of the developed countries women entrepreneurship is growing at a very low rate on the other hand in some developing countries entrepreneurship amongst women is growing at a very fast rate. It is postulated that the disparity in growth of women entrepreneurs in various countries is due to the diversity in the perception of the social and economic milieu prevailing in the society. This paper attempts to explore the characteristics, motivation and challenges faced by the women Entrepreneurs. The paper also explores the factors that differentiate women entrepreneurs in developed countries from women entrepreneurs in developing countries.